Contralateral delay activity is not a robust marker of cognitive function in older adults at risk of mild cognitive impairment. (3rd January 2020) - Farina, Francesca R.; Pragulbickaitė, Gabija; Bennett, Marc; Judd, Cian; Walsh, Kevin; Mitchell, Samantha; O'Connell, Redmond G.; Whelan, Robert
Abstract: Contralateral delay activity (CDA) has been proposed as a pre‐clinical neural marker for mild cognitive impairment (MCI). However, existing evidence is limited to one study with a small sample size ( n  = 24). Our aim was to extend previous work by investigating the relationship between the CDA and MCI risk in a large sample of older adults ( n  = 76). We used a regression approach to determine whether (and when) CDA amplitude predicted MCI risk, as indexed by the Montreal Cognitive Assessment (MoCA). CDA amplitude from ~300‐500 and ~800‐900 ms predicted MoCA performance. However, significant effects were only observed for specific electrodes (P5/P6 and CP3/CP4, but not PO7/PO8) and the nature of the relationship between the CDA and MoCA scores differed across time and according to set size. Bayesian regression analysis indicated partial evidence in favour of the null hypothesis (BF10 values = 4–1.18). Contrary to previous results, our findings suggest that the CDA may not a robust marker of MCI risk. More broadly, our results highlight the difficulty in identifying at‐risk individuals, particularly as MCI is a heterogeneous, unstable condition. Future research should prioritise longitudinal approaches in order to track the progression of the CDA and its association with cognitive decline in later life. Abstract : We investigated whether contralateral delay activity (CDA) was correlated with risk of mild cognitive impairment, defined by Montreal Cognitive Assessment (MoCA) scores, in 76 older adults. The relationship between CDA and MoCA scores differed among electrode sites, stimulus sets and CDA latency. A Bayesian analysis indicated weak evidence for the association between CDA and MoCA scores. These results indicate that CDA is not a robust neural marker of pre‐clinical mild cognitive impairment.